Natural Convection in a Differentially Heated Square Enclosure with a Solid Polygon - R. Roslan; H. Saleh; I. Hashim (The Scientific World Journal)
The aim of the present numerical study is to analyze the conjugate natural convection heat transfer in a differentially heated square enclosure containing a conductive polygon object. The left wall is heated and the right wall is cooled, while the horizontal walls are kept adiabatic. The COMSOL Multiphysics software is applied to solve the dimensionless governing equations. The governing parameters considered are the polygon type, 3≤N≤∞, the horizontal position, 0.25≤X0≤0.75, the polygon size, 0≤A≤π/16, the thermal conductivity ratio, 0.1≤Kr≤10.0, and the Rayleigh number, 103≤Ra≤106. The critical size of the solid polygon was found exists at low conductivities. The heat transfer rate increases with the increase of the size of the solid polygon, until it reaches its maximum value. Here, the size of the solid polygon is reaches its critical value. Further, beyond this critical size of the solid polygon, will decrease the heat transfer rate.